Case Report: Durable response to immuno-chemotherapy in a case of ROS1 fusion-positive advanced lung adenocarcinoma: A case report - Yan, Ningning; Huang, Siyuan; Li, Linlin; Guo, Qianqian; Geng, Di; Zhang, Huixian; Guo, Sanxing; Li, Xingya (Frontiers in Pharmacology, 2022)
Immune checkpoint inhibitor (ICI) has greatly transformed the treatment pattern and improved prognosis of non-small cell lung cancer (NSCLC) without driver gene alterations; however, the benefit of ICI combined treatment in ROS1 fusion positive NSCLC remains unclear. Here, we present a case treated with chemo-immunotherapy achieved a durable response. The patient achieved a partial response (PR) to ICI plus chemotherapy and obtained a 29 months progression-free survival (PFS). In addition, the patient was still in continuous PR status. This case presentation shows ROS1 fusion positive lung adenocarcinoma patients could benefit from ICI plus chemotherapy and ICI combined therapy provide a promising option for ROS1 fusion positive NSCLC.